Isolation of lactobacillus from periodontally healthy subjects and its antimicrobial activity against periodontal pathogens - Azizah Ahmad Fauzi; Zaleha Shafiei; Badiah Baharin; Nurulhuda Mohd (Universiti Kebangsaan Malaysia, 2013)
Bacteriocin or Bacteriocin like inhibitory substances (BLIS) is a protein antibiotic that has a relatively narrow spectrum of killing activity. It could potentially serve as a natural alternative to antibiotics in reducing the development of multi-drug resistant bacteria. Antimicrobial activity of the strains of Lactobacillus sp. isolated from healthy subjects (test strains) against Aggregatibacter actinomycetemcomitans and other periodontal pathogens (indicator strains) isolated from subgingival plaques of aggressive periodontitis patients were determined by using deferred antagonism test and agar-well diffusion method. Strains of Lactobacillus sp., Aggregatibacter actinomycetemcomitans and black pigmented bacteria were selectively isolated from TJA, TSBV and TSBA agars, respectively. Mean diameter zone of inhibition of at least 10 mm was considered as positive results for both methods. Out of 25 strains of Lactobacillus sp. screened, only eight test strains of Lactobacillus sp. showed the specific antimicrobial activity against certain strains of indicator periodontal pathogens during deferred antagonism test. However, out of eight potential strains, only three strains, which were Lactobacillus sp. strain S, Lactobacillus sp. strain V and Lactobacillus sp. strain W consistently showed positive inhibitory activity against black pigmented bacteria by deferred antagonism test and agar-well diffusion method. Therefore, these three strains should be considered as potential BLIS producer strains for further study